The Effect of Role-Playing Learning Model on Student Learning Outcomes in Pancasila Subject in Grade V MIS NU Palangka Raya - Ferkhorya, Asita Nova; Zulkarnain, Ali Iskandar; Sulistyowati, Sulistyowati (-, 2025)
This study aims to describe the implementation and measure the effect of the role-playing learning model on the learning outcomes of applying Pancasila values in the family environment for fifth-grade students at MIS NU Palangka Raya. The study uses a quantitative approach with a one-group pretest-posttest quasi-experimental design. Data were obtained through observation, tests, and documentation, and then analyzed using the T-test. The research results show that role-playing learning was carried out according to the syntax, starting from aperception, group division, scenario provision, acting, discussion, to reflection. Students appeared active, cooperative, and showed an increase in courage and self-confidence. The paired sample t-test showed Sig. (2-tailed) = 0.000 0.05, which means the role-playing model has a positive and significant effect on student learning outcomes. Thus, the role-playing model is effective for use in Pancasila Education learning because it can improve learning outcomes as well as develop students' cognitive, affective, and psychomotor aspects.